2016
DOI: 10.1016/j.ijhydene.2016.04.115
|View full text |Cite
|
Sign up to set email alerts
|

Role of interlayer spacing and functional group on the hydrogen storage properties of graphene oxide and reduced graphene oxide

Abstract: Available online xxxKeywords: Hydrogen storage Graphene oxide Interlayer space Functional group Reduce graphene oxide Structural characterization a b s t r a c t Hydrogen storage properties of the derivatives of graphene, graphene oxide/reducedgraphene oxide are studied in this paper. Modified Hummer's method was adopted for synthesis of graphene oxide (GO) and reduced-graphene oxide (rGO). The morphology of GO/rGO was examined by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 60 publications
2
46
0
Order By: Relevance
“…The morphology of waste EPS beads is spherical with closed pores, as shown in Figure 3. The graphene oxide (GO) was prepared from graphite power by the modified Hummer's method [59][60][61]. The product (GO) was further reduced by hot NaOH solution to obtain rGO [62][63][64].…”
Section: Raw Materialsmentioning
confidence: 99%
“…The morphology of waste EPS beads is spherical with closed pores, as shown in Figure 3. The graphene oxide (GO) was prepared from graphite power by the modified Hummer's method [59][60][61]. The product (GO) was further reduced by hot NaOH solution to obtain rGO [62][63][64].…”
Section: Raw Materialsmentioning
confidence: 99%
“…From the previous research, Raman spectra of graphene and graphene oxide presented similar basal structure profiles with characteristic D band at around 1334cm-1 and G band at around 1590cm -1 . The 2D band in the graphene oxide indicated that all graphitic layer been oxidized [15]. The sample was placed on the glass slide and put under the Raman spectroscopy for characterization.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…3, the Raman spectra obtained display two peaks which at 1361cm -1 and 1596 cm -1 corresponding to the well documented D-band and G-band. The band at 2434cm -1 is known as the 2D band which is indicated that all graphite layers have been oxidized [15]. Compared to the Raman spectra from raw carbon tyre, the peak for D-band and G-band is 1339cm -1 and 1581cm -1 .…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…A small variation in the interlayer distance of graphene can promote dynamical anomalies in the fluid viscosity [48] and diffusion [49] and even in their phase diagram [50]. Additionally, the interlayer separation (d z ) yields important consequences on the graphene membrane's adsorption capacity [51,52].…”
Section: Gas Adsorption: the Influence Of Interlayer Separationmentioning
confidence: 99%